PEMBUATAN WEBGIS PENYAKIT INFEKSI SALURAN PERNAFASAN AKUT (ISPA) DI KABUPATEN JEMBER TAHUN 2013-2015 (THE MANUFACTURE OF WEBGIS FOR ACUTE RESPIRATORY TRACT INFECTIONS (ARI) IN JEMBER REGENCY IN 2013-2015 - Sustin Farlinda; Faiqatul Hikmah; Fahrur Rozi (Jurnal Manajemen Informasi Kesehatan Indonesia (JMIKI), 2018)
Acute Respiratory Infection (ARI) is a common disease in children. Incidence by underage age group is estimated to be 0.29 episodes per child / year in developing countries and 0.05 episodes per child / year in developed countries. Jember Regency Health Office placed ISPA as the top 15 most diseases in Jember Regency, occupying the first position in the highest disease sequence. This study aims to create a WebGIS mapping of ISPA disease to determine the spread of ARI and determine the priority areas of anticipatory and prevention programs of ARI in Jember Regency. The design method uses a waterfall diagram that includes analysis, design, coding, and testing. The result of this research is a WebGIS of Acute Respiratory Infection Disease in Jember Regency in 2013-2015. This digital map has a color that can define the number of ARI events seen from the incidence of ARI cases in each region in Jember Regency, and displays information in each sub-district related to disease info, number of patients and other supporting data. The data analysis showed the highest ARI occurrence in Jenggawah district, Sumberbaru district, Rambipuji district, and Bangsalsari district during 2013-2015.